Assessing Information Literacy Skills of Undergraduate Students: Sample of Ankara University - Özel, Nevzat (Information World, 2016)
Information literacy skills are extremely important for students at universities to keep up with technological innovations and changes, manage the research process effectively and become lifelong learners in the future. Today, people are supposed to be information literate and in this context they are expected to be able to define their information needs, access and evaluate the information resources, construct the new information onto their present knowledge, use the information accordingly and ethically and transmit/present the information. There is a significant contribution of educational activities organized by libraries to equip students with these skills.In this study, it is aimed to determine information literacy skills of undergraduate students at Ankara University in the process of searching, accessing, assessing, using, transmitting/presenting information. The descriptive method has been used and the research has been performed on a sample consisting of 245 undergraduate students selected through stratified random sampling from the universe of 39.136 students. The results have been analyzed through PASW (Predictive Analytics SoftWare).The result of the study indicates that the students encounter difficulties in the subjects which require advanced and more detailed information, they have not received any training for information literacy skills yet and thus they require educational activities which will be organized in this regard.
Keywords: Information literacy; information literacy education; university libraries; students